Impacto da sarcopenia na mortalidade de idosos hospitalizados - Silva, Bruna Souza da (2020)
Sarcopenia is a multifactorial process characterized by a progressive loss of strength, mass and muscle function. This process in the elderly worsens with hospitalization and has shown an association with mortality. Objectives: The objective of this study was to verify the presence of sarcopenia in a tertiary hospital in Cuiabá, MT and to assess its association with the risk of mortality. Methods: Cross-sectional, qualitative and quantitative study, including 251 hospitalized elderly. All the elderly were evaluated by the Charlson Comorbidity Index and by the criteria for classifying sarcopenia by the algorithims proposed by the European Working Group on Sarcopenia in Older People (EWGSOP2) that uses the gait speed test, the calf circumference and handgrip strength. Data on hospitalization date, hospital discharge and mortality were analyzed using the electronic medical record system. Results: 312 were eligible and 251 patients were analyzed, therefore 61 were excluded, with a mean age of 70.87 + 8.05 years. The frequency of sarcopenia was 36.3%, being slightly higher in men, 58.6%. There was no statistically significant difference in the ICC between sarcopenic and non-sarcopenic. Mortality was higher among sarcopenic individuals (8.8%) compared to non-sarcopenic individuals (3.1%, p = 0.049). FPP was lower in the sarcopenic group (16.26 vs 23.45 kg / f, p <0.001), as well as CP (32.74 vs 34.16 cm, p = 0.007). Conclusion: Sarcopenia in elderly patients is a condition that can contribute to hospital mortality.